Optically stimulated luminescence detectors for dosimetry and LET measurements in light ion beams - Christensen, Jeppe Brage; Muñoz, Iván Domingo; Bassler, Niels; Stengl, Christina; Bossin, Lily; Togno, Michele; Safai, Sairos; Jäkel, Oliver; Yukihara, Eduardo Gardenali (Physics in medicine and biology, 2023)
Objective. This work investigates the use of Al2O3:C and Al2O3:C,Mg optically stimulated luminescence (OSL) detectors to determine both the dose and the radiation quality in light ion beams. The radiation quality is here expressed through either the linear energy transfer (LET) or the closely related metric Q eff, which depends on the particle’s speed and effective charge. The derived LET and Q eff values are applied to improve the dosimetry in light ion beams. Approach. OSL detectors were irradiated in mono-energetic 1H-, 4He-, 12C-, and 16O-ion beams. The OSL signal is associated with two emission bands that were separated using a pulsed stimulation technique and subjected to automatic corrections based on reference irradiations. Each emission band was investigated independently for dosimetry, and the ratio of the two emission intensities was parameterized as a function of fluence- and dose-averaged LET, as well as Q eff. The determined radiation quality was subsequently applied to correct the dose for ionization quenching. Main results. For both materials, the Q eff determinations in 1H- and 4He-ion beams are within 5 % of the Monte Carlo simulated values. Using the determined radiation quality metrics to correct the nonlinear (ionization quenched) detector response leads to doses within 2 % of the reference doses. Significance. Al2O3:C and Al2O3:C,Mg OSL detectors are applicable for dosimetry and radiation quality estimations in 1H- and 4He-ions. Only Al2O3:C,Mg shows promising results for dosimetry in 12C-ions. Across both materials and the investigated ions, the estimated Q eff values were less sensitive to the ion types than the estimated LET values were. The reduced uncertainties suggest new possibilities for simultaneously estimating the physical and biological dose in particle therapy with OSL detectors.